PERAN INTERAKSI KEPUASAN KERJA PADA PENGARUH BUDAYA ORGANISASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI (STUDI PADA SEKOLAH TINGGI TEOLOGI GEREJA KALIMANTAN EVANGELIS DI BANJARMASIN) - Hendra; Tinik Sugiati; Maya Sari Dewi (JWM (JURNAL WAWASAN MANAJEMEN), 2018)
This research aims at finding out the role of interaction in job satisfaction (Z) and its influence on exogenous variables: the organizational culture (X1) and competence (X2) for endogenous variables: employee performance (Y) of the Theological College Evangelical Protestant Church in Banjarmasin. This study is an explanatory research with quantitative approach. Primary data have been collected using questionnaires. Research respondents used saturated sample with 31 employees of STT GKE. Data analysis technique to find out the role of interaction on the influence of exogenous variables X1 & X2 on endogenous variables (Y) used Partial Least Square (PLS) analysis technique with Smart PLS 3.0. software. The result of this research concludes that there is an influence of organizational culture (X1) on employee performance (Y) and there is job satisfaction (Z) interaction on the competence of the employee performance (Y). Another finding is that there is no influence of competence variable (X2) on employee performance (Y) and there is no job satisfaction (Z) interaction on organizational culture (X1) influence towards employee performance (Y).